Re-anatomization of conoid and deciduous lateral incisors with direct composite resin - Santezi, Carolina [UNESP]; Bortolatto, Janaína Freitas; Floros, Michael Christopher; de Andrade, Marcelo Ferrarezi [UNESP]; Dovigo, Lívia Nordi [UNESP] (Jaypee Brothers Medical Publishing, 2016)
Discrepancies in tooth size and shape are commonly encountered in the dental clinic, and the conoids lateral incisors are among the most affected. This anomaly affects approximately 1% of the population and it strongly influences the disharmonic characteristics in the smile. This paper reports a clinical case describing a correct diagnosis, planning and the subsequent esthetic treatment of asymmetric lateral incisors using direct composite resin.
Keywords: Composite resin; Conoid teeth; Deciduous teeth; Re-anatomization